2013
DOI: 10.1242/dev.083683
|View full text |Cite
|
Sign up to set email alerts
|

GPI biosynthesis is essential for rhodopsin sorting at the trans-Golgi network in Drosophila photoreceptors

Abstract: SUMMARYSorting of integral membrane proteins plays crucial roles in establishing and maintaining the polarized structures of epithelial cells and neurons. However, little is known about the sorting mechanisms of newly synthesized membrane proteins at the trans-Golgi network (TGN). To identify which genes are essential for these sorting mechanisms, we screened mutants in which the transport of Rhodopsin 1 (Rh1), an apical integral membrane protein in Drosophila photoreceptors, was affected. We found that defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…In a previous study, we identified several mutants that failed to accumulate Rh1 in the rhabdomeres, using retinal mosaic screening of P-element or piggy-Bac inserted lines maintained at stock centers (Satoh et al, 2013). Among them, two lines, KY114446 and KY114472 with P-elements EP2313 and EY07901, respectively, were inserted into the 5′-UTR of Syx5 gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, we identified several mutants that failed to accumulate Rh1 in the rhabdomeres, using retinal mosaic screening of P-element or piggy-Bac inserted lines maintained at stock centers (Satoh et al, 2013). Among them, two lines, KY114446 and KY114472 with P-elements EP2313 and EY07901, respectively, were inserted into the 5′-UTR of Syx5 gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5F), suggesting that most of the Rh1 is degraded 3 h after BLICS in Syx5-deficient photoreceptors. In other mutants associated with Rh1 transport defects, such as Rab6 and PIG mutants, 3 h after BLICS there is a large number of late endosomal compartments and multi-vesicular bodies (MVBs) containing Rh1, indicating that Rh1 is degraded within MVBs, however, it takes more than 3 h to degrade Rh1 in the MVBs (Iwanami et al, 2016; Satoh et al, 2013). Therefore, we conclude that in Syx5-deficient photoreceptors, Rh1 is first transported to Golgi units and is then quickly degraded by MVBs-independent processes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations